The 2018 Prime Minister’s Science Prizes - Editors (New Zealand Science Review, 2019)
The Prizes, now celebrating their tenth year, recognise the impact of science on New Zealanders’ lives, celebrate the achievements of current scientists and encourage scientists of the future. The year’s awards are presented early in the following year. Jim Renwick, past NZAS president (2009–2011) and Professor and Head of School of Geography, Environment and Earth Sciences at Victoria University of Wellington has won the 2018 Prime Minister’s Science Media Communication Prize. In the past five years, Jim has been involved in more than 100 public presentations about climate change, given more than 200 media interviews in New Zealand and internationally, and presented at numerous conferences focused on climate change and how to mitigate its effects. He says he feels a sense of duty to tell the world about the science behind climate change, the consequences that are unfolding, and the urgent need for ac-tion. He will use the prize funds to build collaborations on climate change between artists and scientists and to further strengthen links with tangata whenua. Prime Minister’s Science Prize: The premier award of the Prime Minister’s Science Prizes has been awarded to the STRmix™ team, from the Institute of Environmental Science and Research (ESR). The STRmix™ software interprets DNA material from multiple individuals at a crime scene, and has been used in more than 100,000 cases worldwide. Prime Minister’s MacDiarmid Emerging Scientist Prize: Awarded to outstanding emerging scientist, Dr Peng Du from the Auckland Bioengineering Institute at the University of Auckland. Dr Du’s world-leading research helps the diagnosis and treatment of gut problems. Prime Minister’s Science Teacher Prize: Carol Brieseman from Hampton Hill School in Tawa, Wellington, has been awarded the prize for her work to inspire students, teachers, and communities. As well as encouraging her students to ask difficult questions, Ms Brieseman supports and mentors other teachers, and prompts science initiatives across the school. Prime Minister’s Future Scientist Prize: Awarded to Finnegan Messerli, a former student at Onslow College, Wellington. Finn’s research into the physics problem, why grains of salt form a cone-like pile when poured, will ultimately help scientists better understand the risks of avalanches and slips.